Influence of Notch Sensitivity and Crack Initiation Site on Low Cycle Fatigue Life of Notched Components under Multiaxial Non-proportional Loading (Fracture and Structural Integrity, 2018)
A series of strain-controlled multiaxial low cycle fatigue (LCF) tests under proportional and non-proportional loading conditions have been conducted on notched specimens. Cylindrical bars of Al 6061 aluminum alloy and AISI 316L stainless steel with four values of stress concentration factors referred to the net section Kt,n were employed. The experimental results evidenced a reduction of fatigue life due to non-proportional loading. Furthermore, the crack initiation site has been detected to be moved from the notch tip in the case of steel for high values of notch radius under non-proportional loading. Stress concentration factor evaluated in the elastic field Kt,n has been included in the Itoh-Sakane parameter to evaluate the fatigue life, returning a general underestimation of fatigue life especially for high values of Kt,n. Material notch sensitivity and crack initiation position have been taken into account to further modify the model, improving the original results and showing a better assessment.
Keywords: Non-proportional loading; Notch; Multiaxial loading; Low cycle fatigue; Crack initiation